2020
DOI: 10.1177/0894486520961645
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Ambidexterity in Family-Managed Firms: The Role of Family Involvement in Top Management

Abstract: Organizational ambidexterity is vital for family firms’ long-term success, yet we still lack sufficient insights into the role of family involvement in top management in this context. Building on research on family firm innovation and diversity, we argue there are curvilinear relationships between family involvement in top management and exploration, exploitation, and organizational ambidexterity. We further propose that these (inverse) U-shaped relationships are affected by family CEOs’ family-centered noneco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 145 publications
(285 reference statements)
5
30
0
Order By: Relevance
“…Coherently with recent studies that are exploring family firm heterogeneity in relation to TMT composition (Ro ¨d, 2019), we argue that the presence of non-family members in the TMT is indicative of the degree of network sparseness, a means to access external novel and nonredundant knowledge (Yli-Renko et al, 2001). Research has shown that diversity increases creativity and TMT consisting only in family members misses the external perspective provided by non-family members (Kammerlander et al, 2020). Building on this view, when the TMT is composed of sole family members, it is likely to encounter issues related to a closed and dense social network (Alguezaui and Filieri, 2010) leading to redundant knowledge, thereby limiting the flow of TMT knowledge exchange.…”
Section: Hypothesis Developmentsupporting
confidence: 75%
See 1 more Smart Citation
“…Coherently with recent studies that are exploring family firm heterogeneity in relation to TMT composition (Ro ¨d, 2019), we argue that the presence of non-family members in the TMT is indicative of the degree of network sparseness, a means to access external novel and nonredundant knowledge (Yli-Renko et al, 2001). Research has shown that diversity increases creativity and TMT consisting only in family members misses the external perspective provided by non-family members (Kammerlander et al, 2020). Building on this view, when the TMT is composed of sole family members, it is likely to encounter issues related to a closed and dense social network (Alguezaui and Filieri, 2010) leading to redundant knowledge, thereby limiting the flow of TMT knowledge exchange.…”
Section: Hypothesis Developmentsupporting
confidence: 75%
“…Our findings show that TMT composition and CEO search in concert rather than in isolation are determinants of TMT knowledge exchange and, in turn, of innovation opportunity realization (Cao et al, 2010). In so doing, we combine internal and external perspectives by, respectively, considering the level of TMT knowledge exchange and the network of external contacts of the TMT members and CEO search behavior (Zahra et al, 2007;Kammerlander et al, 2020). Such endeavor allowed us to grasp the mechanisms of absorptive capacity through which family firms acquire external novel knowledge (examining the role of external networks of contacts), assimilate and transform it within the TMT and exploit it to realize innovation opportunities.…”
Section: Introductionmentioning
confidence: 90%
“…To counter these potential business risks, increasing family influence may be accompanied by the family’s strengthened involvement in assessing such risks. This risk evaluation process is again supported by the broad and complementary experiences of various family members (Kammerlander et al, 2020; Kotlar et al, 2020), who may turn this evaluation into a collective learning process (Lumpkin & Lichtenstein, 2005). We argue that the risk-related learning mechanisms and accumulated expertise of families in how to deal with risk over time foster the development of risk management capabilities (Arena et al, 2013; Teece, 2018a).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…We argue that in family-influenced firms, this encouragement grows with increasing family influence due to the growing sensitivity to firm survival. As argued above, increased levels of family influence lead to strengthened ties between family members, intensifying their interactions, and bringing together the complementary expertise of the broader family to address the risks that threaten the business (Cruz & Nordqvist, 2012; Kammerlander, Patzelt, et al, 2020; Kotlar et al, 2020). In turn, the more dynamic the business environment, the more effort the owning family might invest in accumulating risk management expertise (Chirico & Baù, 2014).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…One might argue that the level of indebtedness may affect how females are recruited in the different firms' corporate governance bodies. While perhaps the best way to test this endogeneity problem is by using a two-stage least squares approach [91], the limited available data makes it difficult to identify the appropriate instrumental variables required by this approach [92]. Therefore, to ameliorate this potential endogeneity problem, we use two different methods.…”
Section: Reverse Causalitymentioning
confidence: 99%